The trade restrictiveness of the Multi-Fibre Agreement - Anderson, J; Neary, J (Oxford University Press, 1994)
This study uses the trade restrictiveness index (TRI) of Anderson and Neary (1990) to evaluate U.S. policy toward seven major exporters of textiles and apparel under the Multi-Fibre Arrangement (MFA). The period covered is 1982–88. The MFA controls the shipment of most textile and apparel items to the United States through a system of bilaterally negotiated export quotas that allow for annual growth. The arrangement itself was renegotiated in 1986, with an expansion in the number of items covered and countries included. In addition to these policy changes, changes in economic conditions during the data period altered the restrictiveness of the MFA. The TRI in principle permits all these influences to be accounted for in a consistent manner. The TRI results are contrasted with the standard trade-weighted average tariff equivalent of the quotas. The correlation of the two measures is not significantly different from zero.